Transcriptome profiling based on larvae at different time points after hatching provides a core set of gene resource for understanding the immune response mechanisms of the egg-protecting behavior against Vibrio anguillarum infection in Amphioctopus fangsiao. Issue 124 (May 2022) - Bao, Xiaokai; Wang, Weijun; Yuan, Tingzhu; Li, Yan; Chen, Xipan; Liu, Xiumei; Xu, Xiaohui; Sun, Guohua; Li, Bin; Yang, Jianmin; Feng, Yanwei; Li, Zan
Abstract: Mollusks have recently received increasing attention because of their unique immune systems. Mollusks such as Amphioctopus fangsiao are economically important cephalopods, and the effects of their egg-protecting behavior on the larval immune response are unclear. Meanwhile, little research has been done on the resistance response of cephalopod larvae infected with pathogenic bacteria such as Vibrio anguillarum . In this study, V. anguillarum was used to infect the primary hatching A. fangsiao larvae under different egg-protecting behaviors for 24 h, and a total of 7156 differentially expressed genes (DEGs) were identified at four time points after hatching based on transcriptome analysis. GO and KEGG enrichment analyses showed that multiple immune-related GO terms and KEGG signaling pathways were enriched. Protein–protein interaction networks (PPI networks) were used to search functional relationships between immune-related DEGs. Finally, 20 hub genes related to multiple gene functions or involved in multiple signaling pathways were identified, and their accuracy was verified using quantitative RT-PCR. PPI networks were first used to study the effects A. fangsiao larvae after infection with V. anguillarum under different egg-protecting behaviors. The results provide significant genetic resources for exploring invertebrate larval immune processes. The data lays a foundation for further study the immune response mechanisms for invertebrates after infection. Highlights: This study integrates protein-protein interaction network into transcriptome analysis for the first time in cephalopods. The result lays a function for further exploring invertebrate egg-protecting behavior at the molecular level. It provides valuable gene resources for further study of the immune responses in pathogen-infected invertebrate larvae.